MicroRNA-106b~25 cluster is upregulated in relapsed MLL-rearranged pediatric acute myeloid leukemia - Verboon, Lonneke J; Obulkasim, Askar; de Rooij, Jasmijn D E; Katsman-Kuipers, Jenny E; Sonneveld, Edwin; Baruchel, André; Trka, Jan; Reinhardt, Dirk; Pieters, Rob; Cloos, Jacqueline; Kaspers, Gertjan J L; Klusmann, Jan-Henning; et al. (Oncotarget, 2016)
The most important reason for therapy failure in pediatric acute myeloid leukemia (AML) is relapse. In order to identify miRNAs that contribute to the clonal evolution towards relapse in pediatric AML, miRNA expression profiling of 127 de novo pediatric AML cases were used. In the diagnostic phase, no miRNA signatures could be identified that were predictive for relapse occurrence, in a large pediatric cohort, nor in a nested mixed lineage leukemia (MLL)-rearranged pediatric cohort. AML with MLL- rearrangements are found in 15-20% of all pediatric AML samples, and reveal a relapse rate up to 50% for certain translocation partner subgroups. Therefore, microRNA expression profiling of six paired initial diagnosis-relapse MLL-rearranged pediatric AML samples (test cohort) and additional eight paired initial diagnosis-relapse samples with MLL-rearrangements (validation cohort) was performed. A list of 53 differentially expressed miRNAs was identified of which the miR-106b~25 cluster, located in intron 13 of MCM7, was the most prominent. These differentially expressed miRNAs however could not predict a relapse in de novo AML samples with MLL-rearrangements at diagnosis. Furthermore, higher mRNA expression of both MCM7 and its upstream regulator E2F1 was found in relapse samples with MLL-rearrangements. In conclusion, we identified the miR-106b~25 cluster to be upregulated in relapse pediatric AML with MLL-rearrangements.
Keywords: Multigene Family; RNA, Messenger; histonlysin-N-methyltransferasa; Gene Expression Regulation, Leukemic; Male; MicroRNAs; kohortové studie; Child, Preschool; Histone-Lysine N-Methyltransferase; Up-Regulation; lokální recidiva nádoru; Cohort Studies; Adolescent; transkripční faktor E2F1; Infant; mikro RNA; Child; Minichromosome Maintenance Complex Component 7; dítě; upregulace; akutní myeloidní leukemie; protoonkogenní protein MLL; translokace genetická; mužské pohlaví; regulace genové exprese u leukemie; stanovení celkové genové exprese; klonální evoluce; mladiství; Gene Expression Profiling; Introns; předškolní dítě; Carcinogenesis; Neoplasm Recurrence, Local; introny; lidé; ženské pohlaví; E2F1 Transcription Factor; Humans; Clonal Evolution; karcinogeneze; kojenec; MCM komplex, komponenta 7; Translocation, Genetic; multigenová rodina; Female; messenger RNA; Myeloid-Lymphoid Leukemia Protein; Leukemia, Myeloid, Acute